Optimization of Digital-based Waqf and Its Role in Economic Development in Indonesia - ridwan fauzi; Tatang Astarudin; Badri Khaeruman (Jurnal Sosioteknologi, 2023)
This study aims to analyze the optimization of digital-based waqf in Indonesia and its contribution to economic development. This study uses a qualitative approach through descriptive analysis. The results and discussion of this study show that digital-based waqf has enormous potential in Indonesia; technological advances have helped waqf management with the presence of various platforms from several waqf institutions, as well as new technology in the form of blockchain that can assist in waqf management and, in the end, can contribute to economic development. This study concludes that optimally managed waqf can contribute to creating a prosperous society. The benefits of this research are expected to increase awareness about the importance of waqf and the potential of waqf in Indonesia. This study recommends the parties involved in waqf optimize further the potential of waqf, which is still unexplored.